The Queen and the bird - Saniyasnain Khan; Saniyasnain Khan (New Delhi GOODWORD BOOKS, 2022)
A delightful tale that explores the unexpected friendship between a wise queen and a clever bird. The story unfolds as the bird, with its enchanting songs and insightful observations, brings joy and wisdom to the queen's life. Through their interactions, the queen learns valuable lessons about kindness, humility, and the beauty of nature. This heartwarming story, with its gentle moral teachings, is perfect for young readers, offering a blend of adventure, wisdom, and the magic of friendship.
3-8 grade